O-011 Quantitative MRA is Correlated with Intravascular Pressures Before and After Venous Sinus Stenting: Implications for Treatment and Monitoring. (26th July 2014) - Esfahani, D; Stevenson, M; Moss, H; Amin-Hanjani, S; Aletich, V; Charbel, F; Alaraj, A
Abstract : Introduction: Endovascular stenting is an effective treatment available for patients with clinically significant cerebral venous sinus stenosis. Traditionally, stenting success has been determined by intravascular pressure measurements; new imaging modalities, however, show great potential in documenting improved flow and providing noninvasive monitoring of venous patency after treatment. Quantitative MRA (NOVA, VasSol Inc) is a novel imaging modality that quantifies blood flow using MR imaging. Well established in the arterial system, applications to the cerebral venous sinuses have been limited. In this study, we examined venous QMRA flow in patients before and after venous stenting and correlated these results with intravascular pressure and clinical outcomes Methods: Five patients underwent cerebral venous stenting between 2009 and 2013 at a single institution (Figure 1 ). Preoperatively patients were examined clinically, cerebral venous flow was determined using QMRA, and intravascular pressure measured during angiography. After stenting, intravascular pressure, QMRA flow, and clinical outcomes were repeated and compared Results: An average prestenotic intravascular pressure of 45.2 mmHg (range 31–55) was recorded prior to stenting which decreased significantly to 27.4mmHg (range 16–37) afterwards (paired t-test p = 0.036). The average pressure gradient decreased by 20.4 mmHg. Flow on QMRA increased by 302.3ml/min at the area of stenosis and 304.4 ml/min at the ipsilateral internal jugular vein after stenting. When both jugular veins were considered, the total cerebral venous outflow increased by 260.2 ml/min (Figure 2 ). Statistical analysis of the change in intravascular pressure proximal to stenosis and change in QMRA flow identified a linear relationship (Pearson's correlation r = 0.926). Clinical improvement, including vision, was observed in all patients. Conclusions: Ipsilateral and total venous quantitative flow measurements by QMRA increase after endovascular stenting and correlate with significantly improved intravascular pressures. These findings establish QMRA as a useful adjunct to measure venous flow after stenting, and as valuable tool for noninvasive monitoring of stent patency. Disclosures: D. Esfahani: None. M. Stevenson: None. H. Moss: 1; C; NIH K12 021475, Research to Prevent Blindness (unrestricted departmental grant). S. Amin-Hanjani: 6; C; GE Healthcare, VasSol, Inc. V. Aletich: 2; C; Cordis-Codman. F. Charbel: 2; C; Transonic, Inc. 5; C; VasSol, Inc. A. Alaraj: 2; C; Cordis-Codman.